User migration in the Twitter diaspora - Kristina Radivojevic; D. J. Adams; Griffin Laszlo; Felixander Kery; Tim Weninger (EPJ Data Science)
Abstract User migration across social media platforms has accelerated in response to changes in ownership, policy, and user preferences. This study examines the migration from X/Twitter to emerging alternate platforms such as Threads, Mastodon, and Truth Social. Using a large dataset from X/Twitter, we analyze the extent of user departures and their destination platforms. Additionally, we investigate whether a user’s follower count on X/Twitter correlates with their follower count on other platforms, assessing the transferability of audience size. Surprisingly, our findings indicate that users with larger followings on X/Twitter are more likely to migrate. Moreover, follower counts on X/Twitter are strongly correlated with those on Threads but not with those on Mastodon or Truth Social.